Interviews with collection development managers. Issue 4 (5th October 2015) - Cassell, Kay Ann
Abstract : Purpose: – The purpose of this paper is to present interviews of two collection development managers: David Magier, Princeton University and Daniel Dollar, Yale University. Design/methodology/approach: – The approach was interviews. Findings: – These interviews showed what goes into the thinking of collection development officers in large university libraries. There are probably more similarities than differences. Originality/value: – This is the first of a series of interviews with collection development managers.